South Asian Migration in the Gulf Causes and Consequences (Springer International Publishing, 2018)
This volume explores the reasons behind, and impact of, the migration of South Asian nationals (from India, Bangladesh, Nepal, Sri Lanka, Pakistan, Bhutan and Maldives, Afghanistan and Myanmar) in the Gulf countries (Saudi Arabia, Oman, Kuwait, Qatar, UAE and Bahrain). The authors provide a broad overview of the demographics of the phenomenon, its mechanisms, and focus on the contribution of migrants in various sectors including construction, health and education, and the overall labour market in the Gulf. The book also taps into the regional geo-politics and its links to the South Asian Migration in the Gulf. This book is recommended reading to all those interested in international migration and labour issues.